2000
DOI: 10.2337/diabetes.49.5.701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free fatty acid elevation on postabsorptive endogenous glucose production and gluconeogenesis in humans.

Abstract: . Plasma glucose concentrations decreased by ~10% (P < 0.01), whereas plasma insulin increased by ~47% (P = 0.02) after 9 h of lipid infusion. EGP declined from 9.3 ± 0.5 (lipid) and 9.0 ± 0.8 µmol · kg -1 · min -1 (glycerol) to 8.4 ± 0.5 and 8.2 ± 0.7 µmol · kg -1 · min -1 , respectively (P < 0.01). Contribution of GNG similarly rose (P < 0.01) from 46 ± 4 and 52 ± 3% to 65 ± 8 and 78 ± 7%. To exclude interaction of FFAs with insulin secretion, the study was repeated at fasting plasma insulin (~35 pmol/l) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
189
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(208 citation statements)
references
References 53 publications
16
189
3
Order By: Relevance
“…This has been associated with a NEFA-induced increase in gluconeogenesis [15,16,17,18]. Recently, we have confirmed that the dietary fat-induced increase in gluconeogenesis is associated with increased levels of fructose-1,6-bisphosphatase, a regulatory enzyme in the glucose synthesising pathway [15,19].…”
supporting
confidence: 54%
See 2 more Smart Citations
“…This has been associated with a NEFA-induced increase in gluconeogenesis [15,16,17,18]. Recently, we have confirmed that the dietary fat-induced increase in gluconeogenesis is associated with increased levels of fructose-1,6-bisphosphatase, a regulatory enzyme in the glucose synthesising pathway [15,19].…”
supporting
confidence: 54%
“…Furthermore, it has been suggested that the defect in the suppression of EGP by insulin precedes the defect in insulin action in peripheral tissues [13]. While a high-fat diet might cause peripheral insulin resistance by direct effects on muscle and adipose tissue, the effect of high fat to stimulate gluconeogenesis [15,16,17,18] could have more consequences than simply impaired suppression of endogenous glucose output, as chronic impaired suppression of glucose production leads to obesity and peripheral insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also showed enhanced insulin secretion when plasma NEFA concentrations were increased for 20 min, 90 min or 5 h, by Intralipid and heparin in healthy volunteers [12,13,15]. A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28]. However, no hyperinsulinaemic response has been reported when plasma NEFA concentrations were increased for 5 h to 10 h [29,30] and this turned into an inhibitory effect after a very long-term increase (>24 h) [13,15].…”
Section: Discussionmentioning
confidence: 84%
“…during a glucose load or in type 2 diabetes [4]. Interestingly, the 2 H 2 O and MRS methods yield similar results in healthy humans during fasting [15][16][17] but different results in patients with liver cirrhosis [18] and type 2 diabetes [4], and during NEFA elevation [16,17,19], supporting the idea that glycogen cycling operates differently in diabetes mellitus and certain nutritive conditions.…”
Section: Introductionmentioning
confidence: 87%